West African Economic and Monetary Union : Financial Depth and Macrostability - Imam, Patrick (Departmental Papers; Departmental Paper ;, 2013)
The financial system in the WAEMU remains largely bank-based. The banking sector comprises 106 banks and 13 financial institutions, which together hold more than 90 percent of the financial system's assets (about 54 percent of GDP at end-2011). Five banks account for 50 percent of banking assets. The ownership structure of the sector is changing fast, with the rapid rise of foreign-owned (pan-African) banks. This contributes to higher competition but also rising heterogeneity in the banking system, with large and profitable cross-country groups competing with often weaker country-based (and sometime government-owned) banks. Nonbank financial institutions are developing quickly, notably insurance companies, but remain overall small. This paper presents a detailed analysis of the banking system.